2017
DOI: 10.1039/c7lc00755h
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic step-emulsification in axisymmetric geometry

Abstract: Biphasic step-emulsification (Z. Li et al., Lab Chip, 2015, 15, 1023) is a promising microfluidic technique for high-throughput production of μm and sub-μm highly monodisperse droplets. The step-emulsifier consists of a shallow (Hele-Shaw) microchannel operating with two co-flowing immiscible liquids and an abrupt expansion (i.e., step) to a deep and wide reservoir. Under certain conditions the confined stream of the disperse phase, engulfed by the co-flowing continuous phase, breaks into small highly monodisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 41 publications
0
16
1
Order By: Relevance
“…The formation of droplet in step‐emulsification device can be divided into dripping and balloon mechanisms. It is found that the formation of droplets under dripping mechanism is solely controlled by surface tension . The formation of droplets is hardly affected by the capillary number and the viscosity ratio of both phases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of droplet in step‐emulsification device can be divided into dripping and balloon mechanisms. It is found that the formation of droplets under dripping mechanism is solely controlled by surface tension . The formation of droplets is hardly affected by the capillary number and the viscosity ratio of both phases.…”
Section: Resultsmentioning
confidence: 99%
“…These microfluidic devices usually include T‐junction, cross‐focusing, and coaxial microchannel . In addition to the conventional microdevices, the emerging emulsification device includes triangular cavity, step‐emulsification device, and so on. These devices are usually based on step‐emulsification principle, which are beneficial for the generation of monodispersed droplets or bubbles, as the volume of bubbles or droplets in such devices is mainly determined by the geometric parameters of the equipment and the physical properties of the fluid …”
Section: Introductionmentioning
confidence: 99%
“…The production of these droplets is omitted, as the step-emulsifier is typically much smaller than the size of the channel, allowing for separation of the two processes. 25,35 We note that, although the droplets are already in a cluster initially, their relative rearrangement is still important as it determines the cluster morphology in the final state. The latter results primarily from the droplet-flow interaction and has direct consequence on the photonic properties of the droplet lattice, as we will discuss in details below.…”
Section: Droplet Clusters In Pressure-driven Channel Flowsmentioning
confidence: 94%
“…Here, the focus is on the clustering and droplet interactions within a short distance from their initial release rather than the production of the droplets, which has been studied previously. 25 Our aim is to elucidate the physical picture of the hydrodynamic interactions, potentially improving the design of more efficient microfluidic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Methods of producing monodisperse droplets 1 includes T-junction, 2 co-flow, 3,4 flow-focusing, 5,6 and step emulsification. [7][8][9] Because step emulsification is based on the principle of Laplace pressure, it is insensitive to the flow rate and yields a constant and high monodispersity.…”
Section: All Article Content Except Where Otherwise Noted Is Licensmentioning
confidence: 99%